A review of approaches to manage menu profitability - Lai, Jack Hao Bin; Ab Karim, Muhammad Shahrim; Krauss, Steven Eric; Che Ishak, Farah Adibah (Inderscience, 2020)
A restaurant should be operated with passion but managed by profits. Thus, a successful restaurant often depends on a range of approaches to account for performance and profitability. This review discusses two schools of thought that contribute to managing menu profitability; menu analysis and revenue management. The former focuses on altering menu items to achieve profitability but does not focus much on the consumer aspect. The latter, however, seldom concentrate on menu performance, but instead focuses on employee and guest behaviour, spending patterns, dining periods, and altering management procedures to achieve profitability. This review found that there was no significant research on the association between menu analysis and revenue management approaches. Hence leaves a gap to integrate these approaches to achieve better menu profitability management. On a final note, despite a variety of existing approaches which were proven effective, they were not necessarily practical to be implemented.